2014
DOI: 10.1371/journal.pone.0114492
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Quercetin Reverses Pulmonary Hypertension in Rats

Abstract: Quercetin is a dietary flavonoid which exerts vasodilator, antiplatelet and antiproliferative effects and reduces blood pressure, oxidative status and end-organ damage in humans and animal models of systemic hypertension. We hypothesized that oral quercetin treatment might be protective in a rat model of pulmonary arterial hypertension. Three weeks after injection of monocrotaline, quercetin (10 mg/kg/d per os) or vehicle was administered for 10 days to adult Wistar rats. Quercetin significantly reduced mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…The higher concentrations reported to induce this effect, the mechanism involved (S‐nitrosylation) and the possible K v 7 channel subtypes targeted may explain the differences with respect to our study. Among the different K v 7 channels expressed in vascular smooth muscle (Morales‐Cano et al, , ; Yeung et al, ) including the pulmonary circulation (Joshi et al, ; Morales‐Cano et al, ), Kv7.4 and K v 7.5 channels are considered to play a predominant role in regulating vascular tone (Barrese et al, ). A previous study (Stott et al, ) showed that K v 7.4 currents are increased following the application of cGMP in HEK‐293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The higher concentrations reported to induce this effect, the mechanism involved (S‐nitrosylation) and the possible K v 7 channel subtypes targeted may explain the differences with respect to our study. Among the different K v 7 channels expressed in vascular smooth muscle (Morales‐Cano et al, , ; Yeung et al, ) including the pulmonary circulation (Joshi et al, ; Morales‐Cano et al, ), Kv7.4 and K v 7.5 channels are considered to play a predominant role in regulating vascular tone (Barrese et al, ). A previous study (Stott et al, ) showed that K v 7.4 currents are increased following the application of cGMP in HEK‐293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Its positive effect on hypertension was documented for the first time on spontaneously hypertensive rats, in an experimental model that mimics human hypertension . Since then, many experimental and human studies showed that quercetin exerts vasodilator, antiplatelet, and antiproliferative effects, decreasing oxidative status, blood pressure (BP), and end‐organ damage . The BP‐lowering effect of quercetin is more evident in subjects with certain comorbidities such as metabolic syndrome or in smokers .…”
Section: Introductionmentioning
confidence: 99%
“…19 Since then, many experimental and human studies showed that quercetin exerts vasodilator, antiplatelet, and antiproliferative effects, decreasing oxidative status, blood pressure (BP), and endorgan damage. [20][21][22][23][24] The BP-lowering effect of quercetin is more evident in subjects with certain comorbidities such as metabolic syndrome or in smokers. 25 Different studies tried to establish a connection between the antihypertensive effect of quercetin and certain phenotypes such as the apolipoproteins (apo) E3 and E4, but so far results are conflicting.…”
mentioning
confidence: 99%
“…Quercetin (3,3′,4′,5,7‐pentahydroxyflavone) is one of the main dietary flavonoids, which is found in a variety of beverages, fruits and vegetables, known as a phyto‐oestrogen (Lamson & Brignall, ). Studies showed that quercetin has several bioactivities, including improving intestinal environment, antioxidant, anti‐apoptotic properties (Johinke, De, & Bathgate, ; Morales‐Cano et al., ; Romero et al., ), etc. Previous studies indicated that quercetin increased egg production and feed efficiency in laying hens (Liu et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that quercetin has several bioactivities, including improving intestinal environment, antioxidant, anti-apoptotic properties (Johinke, De, & Bathgate, 2014;Morales-Cano et al, 2014;Romero et al, 2009), etc. Previous studies indicated that quercetin increased egg production and feed efficiency in laying hens (Liu et al, 2013(Liu et al, , 2014.…”
mentioning
confidence: 99%